Techniques for fostering collaboration in online learning communities theoretical and practical perspectives - Pozzi, Francesca 1972-; Persico, Donatella 1957- (Information Science Reference, 2010)
"This book provides a focused assessment of the peculiarities of online collaborative learning processes by looking at the strategies, methods, and techniques used to support and enhance debate and exchange among peers"--Provided by publisher.